Pengaruh Media Audio Visual Terhadap Pengetahuan Dan Keterampilan Petani Di Desa Tincep Kecamatan Sonder Kabupaten Minahasa - Walukow, Miracle Deyf; Pangemanan, Paulus Adrian; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2024)
This research aims to analyze farmers' knowledge and skills in using audiovisual media technology. The study was conducted in Tincep Village, Sonder District, Minahasa Regency, North Sulawesi. The research period was from April to May 2024, encompassing preparation through to the completion of the research report. Data collection methods involved primary data obtained through surveys, interviews, and questionnaires distributed to respondents. Secondary data was collected from journals, theses, and relevant research. The sampling method used was purposive sampling, with a total of 43 respondents selected based on specific criteria using Slovin's formula. The analysis was performed using multiple linear regression with the help of IBM SPSS 26 software. The results indicate that the use of audiovisual media has an impact on farmers' knowledge and skills. The F-test significance value is 0.035, which means the independent variables have a simultaneous effect on the dependent variable. Farmers use audiovisual media to learn agricultural information with the help of applications such as YouTube, Facebook, Google, TikTok, and Instagram, with content including educational materials, tutorials, and promotions.